Synthesis and in vitro antiproliferative activity of new 1-phenyl-3-(4-(pyridin-3-yl)phenyl)urea scaffold-based compounds - Al-Sanea, Mohammad M.; Ali Khan, Mohammed Safwan; Abdelazem, Ahmed Z.; Lee, So Ha; Mok, Pooi Ling; Gamal, Mohammed; Shaker, Mohamed E.; Afzal, Muhammad; Youssif, Bahaa G. M.; Omar, Nesreen Nabil (MDPI, 2018)
A new series of 1-phenyl-3-(4-(pyridin-3-yl)phenyl)urea derivatives were synthesized and subjected to in vitro antiproliferative screening against National Cancer Institute (NCI)-60 human cancer cell lines of nine different cancer types. Fourteen compounds 5a-n were synthesized with three different solvent exposure moieties (4-hydroxylmethylpiperidinyl and trimethoxyphenyloxy and 4-hydroxyethylpiperazine) attached to the core structure. Substituents with different π and σ values were added on the terminal phenyl group. Compounds 5a-e with a 4-hydroxymethylpiperidine moiety showed broad-spectrum antiproliferative activity with higher mean percentage inhibition values over the 60-cell line panel at 10 µM concentration. Compound 5a elicited lethal rather than inhibition effects on SK-MEL-5 melanoma cell line, 786-0, A498, RXF 393 renal cancer cell lines, and MDA-MB-468 breast cancer cell line. Two compounds, 5a and 5d showed promising mean growth inhibitions and thus were further tested at five-dose mode to determine median inhibitory concentration (IC50) values. The data revealed that urea compounds 5a and 5d are the most active derivatives, with significant efficacies and superior potencies than paclitaxel in 21 different cancer cell lines belonging particularly to renal cancer and melanoma cell lines. Moreover, 5a and 5d had superior potencies than gefitinib in 38 and 34 cancer cell lines, respectively, particularly colon cancer, breast cancer and melanoma cell lines.